Analysis of HVDC breakdown characteristic of LLDPE-natural rubber added with biofiller as high voltage insulating material - Nor Izzati Mohd Salleh; Nor Akmal Mohd Jamail; Nishanti Suntharasaka; Nor Shahida Mohd Jamail; Mohamad Farid Sies; Qamarul Ezani Kamarudin; Mohamed Afendi Mohamed Piah (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The influence of solid insulation has been investigated by few researchers. The mechanism of solid breakdown is important in insulation studies. In this research, testing on linear low density polythylene (LLDPE) with natural rubber (NR) and different weight concentration of biofiller are conducted under high voltage direct voltage (HVDC) by using needle and sphere types of electrode arrangements. Oil palm empty fruit bunch (OPEFB) and pineapple leaf fiber (PALF) are the biofillers used for the samples development. The LLDPE-NR samples consists of different weight percentages of biofiller which are 0%, 2.5%. 5.0%. 7.5% and 10% with 3mm thickness. The voltage has been increased until the breakdown occurs. Based on the results obtained, OPEFB and PALF with the highest weight percentages of 10% showed the highest damage voltages of 59.09kV and 59.36kV. It has been proven that both samples with the highest filler content have appropriate insulating properties. In conclusion, the addition of biofiber to LLDPE-NR has improved the breakdown properties compared to pure LLDPE.